(untitled) (Journal of Economic Research & Business Administration, 2018)
The issue of lobbying legislative consolidation is an actual topic for discussion in Kazakhstan. In a number of foreign countries, lobbying activities are in the legal field, while legislation regulating lobbying activities has significant differences. For example, to study foreign experience, the author chose the United States of America, Canada and Germany, which have laws on lobbying with different approaches to the legal regulation. Cause of the absence of a single law on lobbying, kazakh legislation is studied in terms of presenting the possibility of public participation in the development and discussion of draft regulatory legal acts. Based on the analysis, the author pointed out a number of legally fixed opportunities for participation of representatives of individual groups and citizens themselves in the legal activities of executive and legislative bodies. In this regard, the author excludes the need for legislative regulation of lobbying in Kazakhstan on the basis of the norms acting within the framework of interaction of individual groups with representatives of the executive and legislative authorities on the issues of law-making activity. At the same time, in order to increase the transparency of the legislative process, the author proposes a mechanism for entering the Register of organizations operating in the legislature as official representatives of certain groups of persons.